Quantification of MT & CEST MRI for in vivo applications - Carradus, Andrew (2021)
Z-spectroscopy is a form of magnetic resonance imaging (MRI) in which the free water signal is modulated by exchange with other sources of protons resonating at different frequencies. However, interpretation of these signals is not trivial, and care must be taken when attempting to quantify the physical parameters which give rise to these effects. This thesis describes the development of methods to assess and quantify z-spectrum effects, along with in vivo application of these methods with the aim of moving towards clinical use.